Pengembangan Perangkat Pembelajaran Tematik Berbasis Tradisi Tumbu Tanah untuk Menanamkan Nilai Karakter Siswa Sekolah Dasar di Manokwari - Arfiani Arfiani; Aris Munandar; Abdul Saman (Journal on Education, 2024)
This research aims to find out the description of the needs for learning devices owned by elementary schools in Manokwari. This type of research is development research or what is known as Research and Development (R&D). The location of the research was at Elementary School 04 Sanggeng in Manokwari Regency, West Papua Province. The research subjects were fourth grade students at State Elementary School 04 Sanggeng Kab. Manokwari, West Papua Province. The results of data analysis regarding the need for thematic learning tools based on the Tumbu Tanah tradition show that the importance of integrating local culture, such as Tumbu Tanah in learning for student character development in elementary schools, 60% consider the importance of curriculum, guides, learning media and examples of teaching materials based on local culture. Teachers also really need special training and evaluation tools to assess student character. Support from the school is also considered very crucial for the successful integration of local culture in learning.